-66=-5x-7(-4x-7)

Simple and best practice solution for -66=-5x-7(-4x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -66=-5x-7(-4x-7) equation:



-66=-5x-7(-4x-7)
We move all terms to the left:
-66-(-5x-7(-4x-7))=0
We calculate terms in parentheses: -(-5x-7(-4x-7)), so:
-5x-7(-4x-7)
We multiply parentheses
-5x+28x+49
We add all the numbers together, and all the variables
23x+49
Back to the equation:
-(23x+49)
We get rid of parentheses
-23x-49-66=0
We add all the numbers together, and all the variables
-23x-115=0
We move all terms containing x to the left, all other terms to the right
-23x=115
x=115/-23
x=-5

See similar equations:

| -34=8y+6 | | 2−14a=38−2a2-14a=38-2a | | -12+a=60 | | 5(3k+9)-9k=k | | z+1.7=3.8 | | 9x-18=(3x-6) | | 10x+10=15+4x | | -8h=10h-9(-8h+10) | | z+1.7=3/8 | | 3b+5b=32 | | -5-8(7m+5)=-269 | | 6+4x+52=90 | | 25/(x+4)=5 | | -1=p-555 | | 10+4x=3(7+5x) | | 34=20+k | | -3=2x^2-9x | | 2.5-0.7=q | | –6=3p | | 5+5x+5+5x+70=180 | | 4^(10-3x)=256 | | 5p+7.50=40.00 | | 3y+4+5y+18=20 | | 8/(x-5)=8 | | F(x)=|x+3|-2 | | i/4+3=-5 | | (-1/3(12a+18)=5(a-3) | | 24x+16=-2(6x-8) | | 3=9.6+.5x | | H=-16t^2+48t+288 | | 12/(x-6)=4 | | 2(x+12)=3x+14-x |

Equations solver categories